H and HL synergistically regulate jasmonate-triggered trichome formation in tomato. Issue 1 (20th January 2022) - Hua, Bing; Chang, Jiang; Han, Xiaoqian; Xu, Zhijing; Hu, Shourong; Li, Shuang; Wang, Renyin; Yang, Liling; Yang, Meina; Wu, Shasha; Shen, Jingyuan; Yu, Xiaomin; et al.
Abstract: The development of trichomes, which protect plants against herbivores, is affected by various stresses. In tomato, previous studies showed that stress-triggered jasmonic acid (JA) signaling influences trichome formation, but the underlying mechanism is not fully resolved. Here, we found that two C2H2 zinc finger proteins synergistically regulate JA-induced trichome formation in tomato. The naturally occurring mutations in the H gene and its close homolog H-like in a spontaneous mutant, LA3172, cause severely affected trichome development. Compared with the respective single mutant, the h / hl double mutant displayed more severe trichome defects in all tissues. Despite their partially redundant function, the H and HL genes regulate trichome formation in a spatially distinct manner, with HL more involved in hypocotyls and leaves while H is more involved in stems and sepals. Furthermore, the activity of H/HL is essential for JA-triggered trichome formation. The JA signaling inhibitor SlJAZ2 represses the activity of H and HL via physical interaction, resulting in the activation of THM1, a negative regulator of trichome formation. Our results provide novel insight into the mechanism of trichome formation in response to stress-induced JA signaling in tomato.